(Retracted/Ditarik) Quo Vadis Implementasi Konsep Green Constitution Dalam Kebijakan Pembayaran Berbasis Sampah Plastik Pada Surabaya Bus - Ali Murtadho, Nazhif (Jurnal Hukum & Pembangunan, 2024)
This article has been retracted following an internal investigation by JHP in response to complaints from the public and the original author. The article is a plagiarism of a paper submitted for the Scientific Writing Competition at UIN Law Fair 2023, in March 2023. The submitter sent the article in June 2024, while the original authors presented the paper in 2023.